The protective effect of vitamin C, vitamin E and selenium combination therapy on ethanol-induced duodenal mucosal injury - (:unkn) unknown (ARNOLD, HODDER HEADLINE PLC, 2004)
In this study, the effect of a combination of vitamin C, vitamin E and selenium on ethanol-induced duodenal mucosal damage in rats was investigated morphologically and biochemically. The duodenal mucosal injury was produced by oral administration of 1 mL of absolute ethanol to each rat. Animals received vitamin C ( 250 mg/ kg), vitamin E ( 250 mg/kg) and selenium (0.5 mg/kg) for 3 days and absolute ethanol 1 hour after last antioxidant administration and were sacrificed 1 hour after absolute ethanol. Extreme degeneration in intestinal mucosa of rats given ethanol was observed morphologically. In addition, an increase in neuronal nitric oxide synthase immunoreactive areas was observed in the rats of the group given ethanol. On the other hand, a normal morphological appearance and a decrease in neuronal nitric oxide synthase immunoreactive areas were detected in the rats given ethanol + vitamin C + vitamin E + selenium. In the group to which ethanol was administered, an increase in serum cholesterol and a decrease in serum albumin levels were determined. On the other hand, in the group to which ethanol + vitamin C + vitamin E + selenium were administered, serum cholesterol value decreased, and the serum albumin level increased. As a result, we can say that the combination of vitamin C, vitamin E and selenium has a protective effect on ethanol-induced duodenal mucosal injury.
Keywords: duodenal injury; ethanol; nitric oxide synthase; selenium; vitamin C; vitamin E; NITRIC-OXIDE SYNTHASE; FREE-RADICALS; LIPID-PEROXIDATION; OXIDATIVE STRESS; OXYGEN RADICALS; RATS; ALCOHOL; ULCER; DAMAGE; ERYTHROCYTES